Does the Greenspan era provide evidence on leadership in the FOMC? - Makram El-Shagi; Alexander Jung (European Central Bank (ECB), 2013)
The aim of this paper is to examine whether Chairman Greenspan influenced the Reserve Bank Presidents. This question is interesting, because it has been argued that their preferences would be more persistent compared to those of the Governors. We estimate individual Taylor-type reaction functions for the Federal Reserve Districts using their voiced interest rate preferences during the policy go-around as well as real-time economic information on the inflation and unemployment gap. A bootstrap analysis exploits information contained in these reaction functions and constructs counterfactual distributions of disagreement among the Federal Reserve Districts, assuming the absence of factors that could have enforced consensus. We compare these simulated distributions with the observed disagreement during the committee deliberations and find empirical evidence in favour of coordination. This detected coordination helped to bring the preferences of the Federal Reserve Districts more in line with Chairman Greenspan's views.
Keywords: C15; C53; D72; E58; 330; bootstrap; federal Reserve Districts; greenspan era; individual reaction functions; real-time data